Influenza A virus infection of human primary dendritic cells impairs their ability to cross-present antigen to CD8 T cells. - Anna Smed-Sörensen; Cécile Chalouni; Bithi Chatterjee; Lillian Cohn; Peter Blattmann; Norihiro Nakamura; Lélia Delamarre; Ira Mellman (PLoS Pathogens)
Influenza A virus (IAV) infection is normally controlled by adaptive immune responses initiated by dendritic cells (DCs). We investigated the consequences of IAV infection of human primary DCs on their ability to function as antigen-presenting cells. IAV was internalized by both myeloid DCs (mDCs) and plasmacytoid DCs but only mDCs supported viral replication. Although infected mDCs efficiently presented endogenous IAV antigens on MHC class II, this was not the case for presentation on MHC class I. Indeed, cross-presentation by uninfected cells of minute amounts of endocytosed, exogenous IAV was -300-fold more efficient than presentation of IAV antigens synthesized by infected cells and resulted in a statistically significant increase in expansion of IAV-specific CD8 T cells. Furthermore, IAV infection also impaired cross-presentation of other exogenous antigens, indicating that IAV infection broadly attenuates presentation on MHC class I molecules. Our results suggest that cross-presentation by uninfected mDCs is a preferred mechanism of antigen-presentation for the activation and expansion of CD8 T cells during IAV infection.